STUDENT INTEGRATION STRATEGIES WITH DISABILITIES IN A REGULAR SCHOOL - Ferreira, Bárbara; Radeck, Ereni; Irene Padilha Meurer, Letícia (Revista Gênero e Interdisciplinaridade, 2024)
The aim of this article was to introduce the topic Strategies for the Integration of Students with Disabilities in a Regular School. To present, with the aim of advancing the debates on inclusion in the school environment, to understand and evaluate the challenges faced in this process, through various ways and means, strategies for the effectiveness and permanence of students with disabilities in the regular schools of Brazil. As well as, analyze this process of inclusion, as a support for creating an environment in which differences are recognized and then encourage interaction and conviviality with other students and teachers of the institutions. The student is the protagonist of his own journey and for them, teachers need to recognize and seek improvements in their teaching methodologies, aimed at the effectiveness of education and the right of the student. With this, this article addresses pedagogical strategies to promote inclusion in school, its importance and a tool that can be very useful for the teacher and student that is the PEI Individualized Educational Plan, with it the teacher can observe the performance of these students and think in them as individuality, since each has its peculiarities and needs to be respected in its time. Quality education is a right of all to equal conditions to learn and to develop together in the school and social environment.